A Comparative Study of Synthesis, Characterisation and Applications of 5-Salicylidene) Rhodanine and 5-(2-Hydroxy naphthalidene) Rhodanine - Vajpai, Rita; Tiwari, B.M.L.; Tiwari, K.S. (Asian Journal of Chemistry, 2010)
Rhodanine (I) has been refluxed separately with salicylaldehyde and 2-hydroxy napthaldehyde to get 5-substituted rhodanine derivatives (II-III). Their characterisation has been done by chemical and spectral data. The derivatives (II-III) have shown distinctive antibacterial, antifungal and antitubercular activity; and are able to act as specific spot-test and chromatographic spray reagents. Their insecticidal actiyity has been determined with respect to mortality of mosquito larvae, anopheles and culex sp.